Mudharabah Financing Accounting Information System At Bank Muamalat Parepare Sub-Branch Office - Nilam, Adinda; Hamid, Abdul; Ayu Frihatni, Andi (Institut Agama Islam Negeri Parepare, 2022)
The purpose of this study is to find out the mudharabah financing accounting information system at PT. Bank Muamalat KCP Parepare, knowing the output generated from the mudharabah financing accounting information system at PT. Bank Muamalat KCP Parepare, and knows the application of sharia accounting principles in mudharabah financing to PT. Bank Muamalat KCP Parepare. The type of research used in this study is descriptive qualitative research. The results showed that 1) the mudharabah financing accounting information system at PT. Bank Muamalat KCP Parepare is relatively good, because the process of financing transactions up to the repayment process has been carried out with a computer with various types of software that supports the system and reduces the risk of obstacles in the transaction process to its reporting. 2) shows that the internal control of mudharabah financing still has shortcomings in improving and updating the software for the use of information systems used in the financing process, because employees do not understand about it. 3) shows that the mudharabah financing accounting information system at PT. Bank Muamalat KCP Parepare has been applied based on sharia accounting principles, namely the principles of accountability, justice, and truth. These three principles have been applied in the financing process. Keywords: KSPPS Bakti Huria Syariah K.C Parepare, PSAK 101